Provably secure lightweight client authentication scheme with anonymity for TMIS using chaotic hash function - Gaikwad, Vishesh P.; Tembhurne, Jitendra V.; Meshram, Chandrashekhar; Lee, Cheng-Chi (The Journal of supercomputing, 2021)
Telecare medicine information system (TMIS) is recognized as an important tool for improving the quality and protection of healthcare services. In addition to protecting the privacy of patients, many authentication techniques are being introduced in TMIS. After investigations, it is observed that many authentication techniques have security breaches. In this article, we propose an efficient, secure and lightweight authentication scheme for TMIS using chaotic hash function to achieve user anonymity. Chaotic hash function constitutes potential security a set in modern cryptography with its random behavior. Also, we provide the security proof in the random oracle (RO) model and proof of correctness of algorithm is presented using (Burrows–Abadi–Needham) BAN logic for proposed scheme. The comprehensive formal and informal security review demonstrate that the security of our scheme is resistive against known potential attacks. Additionally, our presented authentication scheme performs significantly better as compared to other existing schemes in the literature and also it is efficient on the basis on high security and low cost for computational and communication.